My sister, guard your veil; my brother, guard your eyes uncensored Iranian voices - Azam Zanganeh, Lila (Beacon Press, 2006)
The brief, often breezy essays, reminiscences, reportage and interviews overturn the facile image of Iran as a single, homogenous entity, providing animated discussions of politics, sex, art, women's rights, and racism, poetic culture, underground nightlife, Tehran's Jewish community, censorship, economic inequality and cross-cultural (mis)understanding under a regime that is highly oppressive but continually subverted.